Поліпшення медичних оглядів плавскладу - шлях до збереження здоров'я і працездатності членів екіпажів - Барановська, М.І.; Стовбун, А.І. (Актуальні проблеми транспортної медицини, 2005)
Labour conditions of the water environment specify definite requirements for the crews' level of health. The authors offer to modify the existing national normative acts, and especially the orders of Ministry of Public Health connected to crews' medical examinations. In particular it is offered to estimate level of health in the occupational group under study depending on navigation district, type of a vessel and type of a job fulfilled. Perfection of medical examinations will favour labour conditions improvement and satisfaction of social rights of reverine and marine vessels crews.